Analysis of the causes of vitamin B12 deficiency in different age groups - a review of the literature - Nieciecka, Adrianna; Kędziora-Kornatowska, Kornelia; Lamch, Magdalena; Jabłońska, Monika; Błasik, Natalia; Wójcik, Agata (Journal of Education, Health and Sport, 2022)
Introduction and purpose Vitamin B12 plays an important role in the process of erythropoiesis and the proper functioning of the nervous system. Its source for humans is food, in particular meat, eggs and shellfish. Cobalamin deficiency is a common problem among both geriatric and younger patients. The aim of this review is to analyze the causes of the deficit, to compare its incidence in different age groups and to try to explain potential differences between the groups. A brief description of the state knowledge Cobalamin deficiency can result from many different reasons, such as Addison-Biermer disease, damage to the ileum, use of metformin or proton pump inhibitors, insufficient supply in the diet, and less often genetic disorders. The deficiency phenomenon is more common in the elderly compared to other age groups, especially male patients with multiple comorbidities or in long-term care facilities. On the other hand, among younger people, a higher incidence is observed in the case of high body weight or height. Summary Vitamin B12 deficiency is a common clinical problem, especially among geriatric patients. Most often, cobalamin deficiency may result from reasons related to its improper absorption or deficiency in the diet, while the factors contributing to the deficiency vary depending on the age group. Elderly patients, especially those with additional risk factors, should be carefully monitored for vitamin B12 deficiency.